2009
DOI: 10.1105/tpc.108.064907
|View full text |Cite
|
Sign up to set email alerts
|

Two Chlamydomonas CTR Copper Transporters with a Novel Cys-Met Motif Are Localized to the Plasma Membrane and Function in Copper Assimilation

Abstract: Inducible high-affinity copper uptake is key to copper homeostasis in Chlamydomonas  reinhardtii. We generated cDNAs and updated gene models for four genes, CTR1, CTR2, CTR3, and COPT1, encoding CTR-type copper transporters in Chlamydomonas. The expression of CTR1, CTR2, and CTR3 increases in copper deficient cells and in response to hypoxia or Ni2+ supplementation; this response depends on the transcriptional activator CRR1. A copper response element was identified by mutational analysis of the 5′ upstream re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
109
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 79 publications
(125 reference statements)
2
109
1
2
Order By: Relevance
“…Supplying ascorbate and copper to the lumen of the secretory pathway requires transporters. The copper-handling machinery in Chlamydomonas is similar to that in all eukaryotic cells (Merchant et al, 2006;Page et al, 2009;Blaby-Haas and Merchant, 2012). Cytosolic chaperones deliver the copper they receive from plasma membrane transporters to two highly conserved copper-transporting P-type ATPases.…”
Section: Discussionmentioning
confidence: 96%
“…Supplying ascorbate and copper to the lumen of the secretory pathway requires transporters. The copper-handling machinery in Chlamydomonas is similar to that in all eukaryotic cells (Merchant et al, 2006;Page et al, 2009;Blaby-Haas and Merchant, 2012). Cytosolic chaperones deliver the copper they receive from plasma membrane transporters to two highly conserved copper-transporting P-type ATPases.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have reported that a single Ctr-or COPT-type plasma membrane-localized protein from human (hCtr1; Zhou and Gitschier, 1997), yeast (Sc Ctr3; Pena et al, 2000), mouse (mCtr1; Lee et al, 2000), Arabidopsis (COPT1, 2, 3, and 5; Kampfenkel et al, 1995;Sancenó n et al, 2004), lizard (Ctr1; Riggio et al, 2002), Drosophilia melanogaster (Ctr1A, B, and C; Zhou et al, 2003), or Chlamydomonas reinhardtii (CTR1 and 2; Page et al, 2009) can complement the phenotype of S. cerevisiae ctr1Dctr3D mutant. Rice COPT1 and COPT5, which harbor the conserved motifs and residues required for Cu transport (Puig et al, 2007), have 21 to 51% sequence identity and 35 to 68% sequence similarity with these Ctr or COPT proteins (see Supplemental Table 3 online).…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple members of the COPT (copper transporter) protein family that act in Cu homeostasis by Cu uptake in each analyzed plant species (Kampfenkel et al, 1995;Sancenó n et al, 2004;Page et al, 2009). These COPTs are the homologs of yeast and human Ctr (copper transporter) proteins (Sancenó n et al, 2003;Page et al, 2009). Some Ctrs can interact with themselves or with other Ctr proteins to mediate Cu uptake toward the cytosol (Zhou and Thiele, 2001;Lee et al, 2002;Beaudoin et al, 2006;Nose et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its homologue in Arabidopsis, SPL7, controls nutritional copper homeostasis as well (7,8). Transcriptome experiments revealed multiple targets of this transcription factor in both organisms but besides the genes encoding assimilatory copper transporters (COPT/CTR), which are dramatically up-regulated in both organisms under copper deficiency (9,10), the target genes are distinct (8,11). This may be because modification of the photosynthetic apparatus is a key response in Chlamydomonas but not in Arabidopsis.…”
mentioning
confidence: 95%